Evolving evidence demands for Scotland’s climate policy and potential implications for knowledge brokerage - Ashrika Sharma; Kate Donovan; Anne-Marte Bergseng; Sarah Govan; Pete Smith; Stuart Galloway (Environmental Science & Policy, 2026)

Quantifying impacts of sustainable transport interventions in Scotland: A system dynamics approach - Kathleen Davies; Edward Hart; Stuart Galloway (Transportation Research Part D: Transport and Environment, 2024)

Degradation and lifetime prediction of plastics in subsea and offshore infrastructures - Ibukun Oluwoye; Laura L. Machuca; Stuart Higgins; Sangwon Suh; Tamara S. Galloway; Peter Halley; Shuhei Tanaka; Mariano Iannuzzi (Science of The Total Environment, 2023)

A randomised trial to assess fluid and electrolyte balance responses following ingestion of different beverages in young and older men - Nidia Rodriguez-Sanchez; Stuart D. R. Galloway (European Journal of Applied Physiology, 2023)
Background Older adults are susceptible to dehydration and fluid overload due to a reduced ability to maintain homeostatic control of fluid and electrolyte balance. Purpose To assess fluid and electrolyte balance responses in young and older men following ingestion of commonly consumed beverages differing in composition. Methods 12 young and 11 older men were recruited. Euhydrated body mass was recorded. Participants consumed 1L (250 ml every 15 min) of water, fruit juice, a sports drink or low-fat milk in a randomized cross-over design. Urine and blood samples were obtained before and after the drinking period and every hour thereafter for 3-h. Samples were used to determine osmolality, electrolytes (Na + and K + ), water clearance, and glomerular filtration rate. Results Free water clearance was significantly higher in Young than Older at 1 and 2 h after the ingestion of W and S (p < 0.05). Net Na + and K + balance were not different between Young and Older (p = 0.91 and p = 0.65) adults, respectively. At 3 h Na + balance was negative after ingesting water and fruit juice, but neutral after sport drink and milk. Net K + balance was neutral at 3 h after ingesting milk, but negative after water, fruit juice and sport drink. Conclusions Milk was retained longer than other beverages in Young, but not in Older, despite similar net electrolyte balance responses. Older had higher fluid retention in the first 2 h after the ingestion of all beverages, except for milk when compared to Young, indicating an age-related loss of ability to regulate fluid balance under current study conditions.

The impact of 6-month training preparation for an Ironman triathlon on the proportions of naïve, memory and senescent T cells in resting blood - Cormac Cosgrove; Stuart D. R. Galloway; Craig Neal; Angus M. Hunter; Brian K. McFarlin; Guilllaume Spielmann; Richard J. Simpson (European Journal of Applied Physiology, 2012)